Cation influence in adsorptive propane/propylene separation in ZIF-8 (SOD) topology - Andres-Garcia, Eduardo; López-Cabrelles, Javier; Oar-Arteta, Lide; Roldan-Martinez, Beatriz; Cano-Padilla, Marta; Gascon, Jorge; Mínguez Espallargas, Guillermo; Kapteijn, Freek (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •ZIF-SOD propane/propylene selectivity is ruled by cation substitution.•Cation influences sodalite framework rigidity.•This adsorptive separation process is dominated by kinetics.•Iron promotes a less rigid framework than zinc and cobalt.•ZIF-67 stands out as propylene/propane separation microporous adsorbent. Separation of propylene/propane is one of the most challenging and energy consuming processes in the chemical industry. Propylene demand is increasing and a 99.5% purity is required for industrial purposes. Adsorption based solutions are the most promising alternatives to improve the economical/energetic efficiency of the process. Zeolitic Imidazolate Frameworks (ZIFs) combine the desired characteristics from both MOFs and zeolites: tunability and flexibility from metal organic frameworks, and exceptional thermal and chemical stability from zeolites. In order to enlighten the role of the cation in the sodalite ZIF-8 framework for propane/propylene separation, dynamic breakthrough measurements have been performed over ZIF-8(Zn), ZIF-67 (i.e. ZIF-8(Co)) and MUV-3 (i.e. ZIF-8(Fe)), all isostructural materials based on the same linker (2-methylimidazole). Cation substitution has a remarkable influence in the framework flexibility, and, consequently, in SOD-ZIF selectivity for light hydrocarbons. The differences between the crystallographic pore sizes of the material and the molecular dimensions of propane and propylene are so small, that the slightest change in the framework causes notable advantages/disadvantages in the final application. While cobalt is known to promote a more rigid framework resulting in an adsorption selectivity towards propane, iron presents the inverse effect yielding selectivity to propylene. Zinc has an intermediate effect. A threshold pressure in the isotherm is observed for propylene uptake by ZIF-67 at 273 and 298 K, and only at the lower temperature for ZIF-8. Inlet mixture composition does not highly influence the adsorptive selectivity, although it clearly affects the pure hydrocarbon recovery. Over ZIF-67 breakthrough experiments at 298 K yield a temporary pure propylene flow representing 10–15% of the amount fed. ZIF-67 is a promising candidate for propylene/propane adsorptive separation.